Psychological capital mediates the association between nurses' practice environment and work engagement among Chinese male nurses - Xiaokang Pan; Ting Mao; Jingping Zhang; Jianjian Wang; Pan Su (International Journal of Nursing Sciences, 2017)
Objectives: This study aims to investigate the environmental and individual factors contributing to male nurses' psychological well-being and to explore the psychological mechanisms that may explain the links between nurses' practice environment and work engagement, thereby presenting the implications for nurse managers. Methods: A total of 161 male nurses from three tertiary first-class hospitals in Changsha City in China participated in the study. We collected the data using the Practice Environment Scale of the Nursing Work Index, the Psychological Capital Questionnaire, and the Utrecht Work Engagement Scale. Results: Scores of male nurses' practice environment (2.88Â Â±Â 0.31), psychological capital (4.42Â Â±Â 0.62), and work engagement (3.17Â Â±Â 1.39) were all above the midpoint; however, the subscales âthe nursing staffing and resources adequacyâ (2.72Â Â±Â 0.48), âhopeâ (4.33Â Â±Â 0.72), and âdedicationâ (2.96Â Â±Â 1.61)scored lowest. Nurses' practice environment and psychological capital positively predicted nurses' work engagement; psychological capital fully mediated the influence of nurses' practice environment on work engagement. Conclusions: Creating a supportive nursing practice environment can increase male nurses' work engagement by developing their psychological capital. Nurse managers can then provide reasonable workload and pathways for male nurses to achieve goals, thereby fostering their hope. Keywords: Male nurses, Nurses' practice environment, Psychological capital, Work engagement